Development of two-dimensional virtual fitting room in web based environment - Naadiyah Haris, 1994-, author; Nor Erne Nazira Bazin, supervisor; Fakulti Komputeran (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Sains Komputer (Perisian Grafik dan Multimedia)) - Universiti Teknologi Malaysia, 2017